GROWTH-PROMOTING MICROORGANISMS IN THE DEVELOPMENT OF ORCHID SEEDLINGS OF PHALAENOPSIS, CYMBIDIUM, AND DENDROBIUM GENERA - de Medeiros, Lorena Bezerra [UNESP]; de Souza, Antonio Maricélio Borges [UNESP]; Vieira, Guilherme Rodrigues [UNESP]; Ferreira, Kássia Barros [UNESP]; Campos, Thiago Souza [UNESP]; Pivetta, Kathia Fernandes Lopes; Rigobelo, Everlon Cid (PPUFU - Portal de Periódicos da Universidade Federal de Uberlândia, 2023)
The demand for sustainable agricultural production systems is increasing, and using growth-promoting microorganisms in plants has stood out because it decreases or even replaces chemical fertilizer use, reducing production costs. This study aimed to evaluate the response of some microorganisms applied to the seedlings of primary orchids cultivated in Brazil (Phalaenopsis sp. 'Taisuco Swan', Cymbidium atropurpureum, and Dendrobium secundum). The experimental design was completely randomized. There were seven treatments (absence of microorganisms – control, Trichoderma sp. in sodium alginate, Trichoderma sp. in clay, Trichoderma sp. in sodium alginate and clay, Trichoderma sp. in a liquid medium, Azospirillum brasilense + Bacillus subtilis in a liquid medium, and Bacillus pumilus in a liquid medium), four replications, and three plants per plot. The seedlings were grown in a greenhouse and evaluated 190 days after microorganism inoculation. The evaluation of morpho-physiological characteristics differed according to the particularities of each genus. The Bacillus pumilus and Azospirillum brasilense + Bacillus subtilis rhizobacteria in a liquid medium for Phalaenopsis sp. 'Taisuco Swan' and the Trichoderma sp. fungus in a liquid medium for Cymbidium atropurpureum increased seedling growth and development. Azospirillum brasilense + Bacillus subtilis in a liquid medium for the Dendrobium secundum orchid promoted more root biomass. Using beneficial microorganisms in orchid cultivation is promising, and seedling growth and development depend on their inoculation and the morpho-physiological characteristics of each plant.
Keywords: Azospirillum brasilense; Bacillus pumilus; Bacillus subtilis; Orchidaceae; Trichoderma sp